THE ILLUSION OF HAPPINESS: INVESTIGATING THE PHENOMENON OF “FAKE HAPPY MARRIAGES” IN CONTEMPORARY SOCIETY - Hossin, Aisah; Jumrah, Mohd Hanafi (Universitas Mercu Buana, 2025)
Social media plays a significant role in contemporary society, surpassing traditional media like radio and television. Nevertheless, its impact becomes pronounced when individuals exceed reasonable engagement limits. These platforms encourage sharing personal moments using manipulation tools that alter the appearance of pictures, creating an illusion of perfection. Consequently, this portrayal on platforms like Facebook, Instagram, and WhatsApp can influence perceptions, fostering an unrealistic ideal of a happy marriage and life. So, this study investigates the phenomenon of “fake happy marriages” in contemporary society through social media and to see what tools or apps are usually used by the couple to show their happy marriage using the self-representation theory from the sociological perspective. This study used the qualitative method of one-to-one interviews, which involved eight informants including four males and four females using the purposive sampling method. The findings showed the couples represent themselves to the media by concerning society's worldview and expectation in terms of representing themselves as an ideal married couple even though it's different from their real life. Other than that, people will create fake happy moments to fill the loneliness and protect the relationship from being sniffed out by family and friends. The motive of this fake happy marriage is to arouse jealousy or admiration for other people like ex-couples and scandals.